2013
DOI: 10.1037/a0033224
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the borderlands: The roles of minority stressors, bicultural self-efficacy, and cognitive flexibility in the mental health of bisexual individuals.

Abstract: The present study examined the relations of minority stressors (i.e., experiences of prejudice, expectations of stigma, internalized biphobia, outness/concealment of bisexuality) as well as posited mental health promoters (i.e., bicultural self-efficacy, cognitive flexibility) with psychological distress and well-being in a sample of 411 bisexual people. Most of the minority stress variables were related positively with psychological distress and negatively with well-being, whereas the mental health-promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
207
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 74 publications
19
207
7
3
Order By: Relevance
“…The study thus identified three mediating processes that are risk factors for psychological distress among sexual minorities who are faced with perceived discrimination. These findings also underscore the importance of expectations of rejection and suggest that the associations between perceived discrimination and general mediators are more complex than previous research (e.g., Brewster et al, 2013;Feinstein et al, 2012) had revealed.…”
Section: Covariates Education Agementioning
confidence: 56%
“…The study thus identified three mediating processes that are risk factors for psychological distress among sexual minorities who are faced with perceived discrimination. These findings also underscore the importance of expectations of rejection and suggest that the associations between perceived discrimination and general mediators are more complex than previous research (e.g., Brewster et al, 2013;Feinstein et al, 2012) had revealed.…”
Section: Covariates Education Agementioning
confidence: 56%
“…For instance, the internalization of stigma (i.e., proximal stress) can also be considered as a mediator of the associations between distal stress and health (Brewster et al, 2013; Hatzenbuehler, 2009). In addition, the minority stress model has not adequately taken into account general mediating psychological processes; some of the mediating processes posited and supported with some research have focused on coping and emotional regulation, social processes (e.g., support, isolation), and cognitive processes (e.g., hopelessness, expectancies; Brewster et al, 2013; Denton et al, 2014; Hatzenbuehler, 2009). As such, more complex models attending to underlying individual and contextual factors related to both physical and mental health are needed.…”
Section: Minority Stress and Sexual Minority Healthmentioning
confidence: 99%
“…For example, bisexual women in relationships with multiple female and male partners may have greater visibility as a bisexual individual than bisexual women with a single male or female partner, which in turn may influence their experiences with stigma, outness as a sexual minority, and internalized stigma. Proximal and distal minority stressors have been associated with elevated levels of mental health problems and substance use among LGBT populations (Brewster, Moradi, DeBlaere, & Velez, 2013; Herek & Garnets, 2007; Hughes & Eliason, 2002; Mays & Cochran, 2001; Waldo, 1999; Weber, 2008). Given this, mental health problems and substance use may vary across current intimate relationship status among bisexual women, and minority stressors may mediate these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found that bisexual women in a relationship with a single male partner were less open about their sexual orientation (Dyar, Feinstein, & London, 2014; Li et al, 2013, Canada). Although not being visible as a bisexual individual may decrease experienced bi-negativity from heterosexual communities (Mays & Cochran, 2001; Li et al, 2013, Canada), being less out can also lead to greater internalized bi-negativity (Brewster et al, 2013). Bisexual women in a relationship with a single female partner conversely may be more “out” as a sexual minority, in part due to a more consistent visibility of their same-gender attractions.…”
Section: Introductionmentioning
confidence: 99%